Effects of transport on the metabolism of horses - Yáñez Pizaña, Ariadna; Roldan Santiago, Patricia; Mora Medina, Patricia; Borderas Tordesillas, Fernando; Flores Peinado, Salvador; Mota Rojas, Daniel (Revista Científica de la Facultad de Ciencias Veterinarias, 2012)
Ver resumen pdf.